NILAI MORALITAS KEPEMIMPINAN PENDIDIKAN ISLAM - Wahab, Jamal (Inspiratif Pendidikan, 2020)
The terms used by Qur'an in discussing leadership are al-Imam, al-khilafah, Ulil amri, and Al-Mulk. Leadership is the ability and readiness for someone to know, to guide, to direct and to motivate others so that they work to achieve the same goals. The morality values of Islamic leadership prioritize religiosity which is integrated with moral values. These moral values include humanity, social, and aegis values. Religiosity leads a leader to act, decide, organize, and run the system based on Qur'an and hadith. Ethical leadership makes the atmosphere of work relations in an organization or an Islamic educational institution more comfortable and avoids vertical or horizontal conflicts.